Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the value of [tex]\( b^2 - 4ac \)[/tex] for the given quadratic equation [tex]\( 2x^2 + 3x = -1 \)[/tex], follow these steps:
1. Rewrite the equation in standard form:
The standard form of a quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex]. So we need to bring all terms to one side of the equation.
[tex]\[ 2x^2 + 3x + 1 = 0 \][/tex]
2. Identify the coefficients:
From the standard form equation [tex]\( 2x^2 + 3x + 1 = 0 \)[/tex]:
[tex]\[ a = 2, \quad b = 3, \quad c = 1 \][/tex]
3. Calculate the discriminant:
The discriminant of a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] is given by [tex]\( b^2 - 4ac \)[/tex].
Substituting the values of [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ b^2 - 4ac = 3^2 - 4 \cdot 2 \cdot 1 \][/tex]
4. Perform the arithmetic operations:
[tex]\[ b^2 - 4ac = 9 - 8 = 1 \][/tex]
Hence, the value of [tex]\( b^2 - 4ac \)[/tex] for the equation [tex]\( 2x^2 + 3x = -1 \)[/tex] is [tex]\( 1 \)[/tex].
So, the correct answer is:
[tex]\[ 1 \][/tex]
1. Rewrite the equation in standard form:
The standard form of a quadratic equation is [tex]\( ax^2 + bx + c = 0 \)[/tex]. So we need to bring all terms to one side of the equation.
[tex]\[ 2x^2 + 3x + 1 = 0 \][/tex]
2. Identify the coefficients:
From the standard form equation [tex]\( 2x^2 + 3x + 1 = 0 \)[/tex]:
[tex]\[ a = 2, \quad b = 3, \quad c = 1 \][/tex]
3. Calculate the discriminant:
The discriminant of a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] is given by [tex]\( b^2 - 4ac \)[/tex].
Substituting the values of [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ b^2 - 4ac = 3^2 - 4 \cdot 2 \cdot 1 \][/tex]
4. Perform the arithmetic operations:
[tex]\[ b^2 - 4ac = 9 - 8 = 1 \][/tex]
Hence, the value of [tex]\( b^2 - 4ac \)[/tex] for the equation [tex]\( 2x^2 + 3x = -1 \)[/tex] is [tex]\( 1 \)[/tex].
So, the correct answer is:
[tex]\[ 1 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.